Distinct effects of polyphenols and solvents on dentin collagen crosslinking interactions and biostability. Issue 12 (December 2021) - Hass, Viviane; Liu, Hang; Cook, Walter; Walker, Mary P.; Wang, Yong
Abstract: Objective: To evaluate the effects of different polyphenols and solvents on dentin collagen's crosslinking interactions and biostabilization against MMPs and collagenase degradation. Methods: Two polyphenols [proanthocyanidin (PA) and quercetin (QC)] with different water solubility were prepared as treatment solutions using ethanol (EtOH) or dimethyl sulfoxide (DMSO) as solvents. 6-um-thick dentin films were microtomed from dentin slabs of third molars. Following demineralization, films or slabs were subject to 60-s treatment (PA or QC) or no treatment (control) with subsequent extended-rinse with original solvent (EtOH or DMSO) or distilled water (DW). Collagen crosslinking interactions were assessed by FTIR. Biostability was assessed through endogenous MMPs activity via confocal laser scanning microscopy, and exogenous collagenase degradation via weight loss, hydroxyproline release and SEM. Finally, direct collagenase inactivation was also evaluated. Data were analyzed by three-way ANOVA and post-hoc tests ( α = 0.05%). Results: Distinct effects of two polyphenols and solvents on collagen crosslinking and biostabilization were observed. Higher crosslinking and biostability efficacy occurred with PA than QC (p < 0.001) that demonstrated negligible collagen interactions. With DMSO solvent, efficacy results were significantly reduced with both polyphenols (p < 0.05). DMSO-rinse further weakened interactions of PA with collagen, diminishing biostability (p < 0.05). Low biostability was detected with QC and DW-rinse, suggesting direct enzymatic inhibition due to physical presence in collagen. Significance: Collagen crosslinking interactions and biostability depend on polyphenol chemical characteristics. Treatment-solution solvents may affect interactions between polyphenols and collagen, specifically, DMSO showed detrimental effects on collagen crosslinking and biostability and should be used with caution.